Ideologi Pendidikan Pragmatis dan Relevansinya dengan Ketersediaan Lapangan Pekerjaan - Eneng Humaeroh (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
The job field does not fully absorb educated graduates, on the contrary, graduates are not all able to get job opportunities in accordance with the field of science studied. This is because the education taken has less correlation with the needs of the industrial or business world. This research tries to explore the Pragmatic Education Ideology which is education oriented towards preparing educated and skilled personnel. Education that focuses on output in the form of providing quality human resources. This research approach uses a qualitative approach with primary source in the form of research journals related to pragmatic education and job availability and the correlation between the two. Based on the analysis of the theories found, there is significant relevance, in how pragmatic education is the basis for providing jobs, especially through the growth of MSMEs, the creative economy, and the digital economy.